THE GENERIC NAMES PROPOSED FOR HYMENOMYCETES-II* Hymenolichenes - DONK, M. A. (Research Center for Biology, 1954)
1. This part deals with the generic names proposed for Hymenolichenes, a very limited group of Hymenomycetes. 2. In connection with Herpothallon Tobl. attention is drawn to Hypochnus Fr. ex Ehrenb. (non Fr. ex Fr.), which seems to be the correct name for the genus.